2011
DOI: 10.4081/gh.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors associated with pandemic influenza A (H1N1) hospitalization rates in California, USA: a geospatial analysis

Abstract: Abstract. The 2009 H1N1 influenza A virus subtype (H1N1) pandemic had a large impact in the United States of America (USA), causing an estimated 192,000 to 398,000 hospitalizations and 8,720 to 18,050 deaths between April 2009 and midMarch 2010. Recent research on the 2009 H1N1 pandemic has largely focused on individual, non-spatial demographic characterizations (e.g. age and race/ethnicity) associated with H1N1 hospitalizations. Broader ecological factors such as transportation use, land use and other socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 47 publications
0
25
1
1
Order By: Relevance
“…Additional differences in the susceptibility of a population to the pandemic H1N1 influenza virus may have biased an ecologic analysis, thus, data on at-risk populations, including the proportion of older individuals, degree of obesity, and pregnancy rate were considered. Further parameters, including public transportation usage and population density, were found to be related to hospitalization rates during the H1N1 pandemic in an ecologic analysis from California [20]. Population density was not found to be related to H1N1 mortality or NAI supply in this analysis, however.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Additional differences in the susceptibility of a population to the pandemic H1N1 influenza virus may have biased an ecologic analysis, thus, data on at-risk populations, including the proportion of older individuals, degree of obesity, and pregnancy rate were considered. Further parameters, including public transportation usage and population density, were found to be related to hospitalization rates during the H1N1 pandemic in an ecologic analysis from California [20]. Population density was not found to be related to H1N1 mortality or NAI supply in this analysis, however.…”
Section: Discussioncontrasting
confidence: 64%
“…Population density was not found to be related to H1N1 mortality or NAI supply in this analysis, however. It is likely that population density may have a greater impact on total hospitalizations and the spread of influenza, but that different factors related to health spending and health care infrastructure have a greater impact on H1N1 mortality, as was found in this analysis and by Nikolopoulos, et al [18] While every attempt was made to adjust for the many differences between Member States that could possibly bias an association between NAI supply and H1N1 mortality, the included co-factors were by no means exhaustive and several important confounders such as air quality or land use patterns – which may impact a population's susceptibility to influenza or exposure to infected livestock – may continue to bias the estimated main effect [18], [20]. Further, as with any ecological study, these associations may not be reflective of the individual-level association, and evidence from controlled studies is needed to evaluate the possibility of a causal relationship between NAIs and influenza mortality.…”
Section: Discussionmentioning
confidence: 67%
“…According to Freedman and Leder [40], transport networks by virtue of direct contact with large numbers of individuals allow greater spread of pathogens and make populations exposed to public transport systems most susceptible to infection. Maliszewski e Wei [41] also found that public transport use rates were significantly and positively associated with hospitalization rates related to influenza A (H1N1) 2009 in California in the United States.…”
Section: Discussionmentioning
confidence: 95%
“…These results are consistent with a number of previous investigations examining demographic factors associated with influenza cases or deaths in temperate climates. For example, previous investigators examining ecological factors associated with pandemic influenza A (H1N1) hospitalization rates in the state of California revealed hospitalization rates were spatially dependent [18]. As another example, transmission of influenza A and B in a Pennsylvania school-based study population revealed that race was a significant mediating factor [19].…”
Section: Discussionmentioning
confidence: 99%